Analysis of The Determinants of Bank’s Credit Risk：An Empirical Study of Commercial Banks in China - Li, Haoyu (2017)
Even though the sub-prime credit risk has passed for a long time, the concern about credit risk remains high. China, as presently one of the most important developing countries in the world, its banking system remains many problems and these financial problems would have severe negative impacts on not only Chinese economy but also some economy related to China. After years’ efforts of the Chinese government in reforming and adjusting the ownership structure of China's commercial banks, there are now various types of commercial banks in the banking industry. This dissertation is to investigate whether the macroeconomic and microeconomic determinants of credit risk across different types of commercial banks with different ownership structure would be different. The data are obtained from 16 listed China’s commercial banks over the period of 2011 to 2016. The sample banks are divided into three groups by their ownership structure, namely, state owned commercial banks, joint stock commercial banks and city commercial banks. And the reason for choosing the period of 2011 to 2016, is that this period of time includes the period of rapid growth of the economy as well as the downturn of economic growth in the recent years. In this study, the examining model applied is panel data model and the NPL ratio will be used as a measure of credit risk. The variables going to be examined include both macroeconomic factors such as GDP, inflation ratio and money supply growth, and microeconomic factors included total assets, earning assets to total assets, leverage, net interest spread, regulatory capital, loan-to-deposit ratio and loan loss provision. After the brief introduction of the research background and purpose in section 1, the detailed description of credit risk is present in section 2 in the respects of definition, impacts on banks and the economy, widely applied measurement and management and proximate causes of credit risk that are summarised from previous literature, also there are some literature reviews that relate to the main hypothesis present in this section. In section 3, it focuses on introducing the credit risk condition of China’s banking industry, and discussing the proximate causes of credit risk in Chinese market, according to its recent economic conditions and some policies made by governments. In section 4, the methodology and variables applied are introduced, following with the simple statistical analysis of the sample data and brief examining process. In the following section, the analysis of regression results is present, and the finding shows clearly that the determinants of credit risk across different types of commercial banks with different ownership structure are different, the macroeconomic factor would have more impact on credit risk in the group of city commercial banks, the results of bank-specific factors are varied. In the conclusion part, along with the conclusion of the study, some suggestions for China’s banking industry are also present in the respects of commercial banks, policy makers and regulators.